Acute Diuretic Activity Of Alcoholic Extracts Of Hygrophila Auriculata Seeds In Normal Wistar Albino Rats - PREETHI GP; GOPALAKRISHNA HN; RATHNAKAR UP; DURGA P; VISHNU; JNANESHWARA SHENOY (International Journal of Pharma and Bio Sciences, 2012)
The present study was undertaken to investigate the diuretic properties of the seeds of Hygrophila auriculata (Schum) (Acanthaceae) in normal Wistar Albino rats. Alcohol extracts of seeds of H. auriculata (300mg/kg and 500mg/kg p.o.) were investigated for diuretic activity by measuring the total urine output over 24hrs and electrolytes (Sodium, Potassium and Chloride) estimation in Wistar rats (n=6). Frusemide (20 mg/kg, p.o), a high ceiling diuretic served as positive control and normal saline (25 ml/kg, p.o) as placebo control. The urine volume was 3.33 ±0.13ml, 9.12 ± 0.25 ml, 3.1833 ± 0.15ml and 5.52 ±0.18 ml for control, frusemide, extract at 300mg/kg and 500mg/kg dose respectively. There was significant increase in sodium (198.33 ± 2.99 m.mol/L), potassium (97.67 ± 2.33 m.mol/L) and chloride ion excretion (132.67 ± 2.65 m.mol/L) in the 500mg/kg alcohol extract as compared to control group (107 ± 2.11 m.mol/L, 55 ± 4.09 m.mol/L & 87.33 ± 2.33 m.mol/L respectively) (P < 0.001).The alcoholic extract of H.auriculata showed significant diuretic properties. At both the doses employed there was a significant increase in electrolyte excretions, however increase in urine volume was significant only at 500mg/kg. Further studies elucidating mechanism of action and employing lower doses are warranted.